Business networks and innovation: The case of a network in the cosmetic industry in Bogotá (Colombia) (2011)
A method of encouraging business innovation is participation in associative processes, such as enterprise networks. The aim of this study was to identify actions favoring innovation in a group of companies that established a business network in the cosmetic industry in Bogotá, Colombia. We used a questionnaire based on the concept of innovation described in the Oslo Handbook (OECD, 2005), and analyzed data using graph theory. The results indicate that companies innovate, but they make few investments in acquiring knowledge. We also found that companies develop actions for internal improvement more frequently than they generate improvements in relationships with other actors in the network. © 2010 Universidad Icesi. All rights reserved.